Rozie Times: Malaysia's largest university made history in the Malaysia Book of Records with its 95th convocation ceremony / Galeri Seni Tuanku Nur Zahirah - Universiti Teknologi MARA, Galeri Seni Tuanku Nur Zahirah (GESTURZ) (Galeri Seni Tuanku Nur Zahirah, UiTM, 2023)
Rozie Times 4 continues chronicling the events and achievements of UiTM alongside Datuk Rozie, now past her 400th day in office. From the articles we learn of numerous MoUs signed and partnerships forged, charitable and social enterprises undertaken, appointments and accomplishments made, all communicated in her conversational style. Once again her love and pride for Keluarga UiTM were evidenced, as she jotted down the names and personally thanked individuals from various faculties, departments, centres, offices, organisations and communities that have made an impression. Rozie Times shares essence of the Vice-Chancellor's distinctive leadership and viewpoints.